Uniqueness and Nonuniqueness of the GNSS Carrier-Phase Compass Readings - Teunissen, Peter (Springer, 2012)
In this contribution we analyse the possible nonuniqueness in the least-squares solution of the GNSS carrier-phase compass model. It is shown that this lack of uniqueness may manifest itself in the fixed baseline estimator and therefore in the GNSS compass readings. We present the conditions under which nonuniqueness occurs and give explicit expressions for these nonunique least-squares solutions.